36.2k views
0 votes
I Need to find the Function Operations​

I Need to find the Function Operations​-example-1

1 Answer

2 votes

Answer:

1)
(f+g)(x)=2x^2+3x-6

2)
(f-g)(x)=2x^2+x

3)
(f \cdot g)(x)=2x^3-4x^2-9x+9

Explanation:

So we have the two functions:


f(x)=2x^2+2x-3\text{ and } g(x)=x-3

And we want to find (f+g)(x), (f-g)(x), and (f*g)(x).

1)

(f+g)(x) is the same to f(x)+g(x). Substitute:


(f+g)(x)=f(x)+g(x)\\=(2x^2+2x-3)+(x-3)

Combine like terms:


=(2x^2)+(2x+x)+(-3-3)

Add:


=2x^2+3x-6

So:


(f+g)(x)=2x^2+3x-6

2)

(f-g)(x) is the same to f(x)-g(x). So:


(f-g)(x)=f(x)-g(x)\\=(2x^2+2x-3)-(x-3)

Distribute:


=(2x^2+2x-3)+(-x+3)

Combine like terms:


=(2x^2)+(2x-x)+(-3+3)

Simplify:


=2x^2+x

So:


(f-g)(x)=2x^2+x

3)

(f*g)(x) is the same to f(x)*g(x). Thus:


(f\cdot g)(x)=f(x)\cdot g(x)\\=(2x^2+2x-3)(x-3)

Distribute:


=(2x^2+2x-3)(x)+(2x^2+2x-3)(-3)

Distribute:


=(2x^3+2x^2-3x)+(-6x^2-6x+9)

Combine like terms:


=(2x^3)+(2x^2-6x^2)+(-3x-6x)+(9)

Simplify:


=2x^3-4x^2-9x+9

So:


(f \cdot g)(x)=2x^3-4x^2-9x+9

User Ram Madhavan
by
4.2k points